Influence of well-being variables and recovery state in physical enjoyment of professional soccer players during small-sided games - Selmi, O.; Gonçalves, B.; Ouergui, I.; Sampaio, J.; Bouassida, A. (Research in Sports Medicine, 2018)
This study aimed to assess the effects of the total quality of recovery and well-being indices (self-ratings of sleep during the preceding night, stress, fatigue and delayed onset muscle soreness) on rating of perceived exertion (RPE) and physical enjoyment (PE) during small-sided games. A total of 20 professional soccer players (25 ± 0.8 years) completed four 5-a-side game sessions of 25-min duration each (4 × 4 min work with 3-min passive recovery in-between). All variables were collected before each game session with the exception of RPE and Physical Activity Enjoyment Scale that were collected after. The results demonstrate that recovery state and pre-fatigue states were not contributing signals of affected internal intensity and enjoyment of players. The study established the objectivity and utility of RPE as a useful tool for determining internal intensity during soccer-specific training as well as PE for assessing emotional response during exercise or training session.